Factors influencing financial planning for marriage amongst young Malaysian couples - Nga, Joyce Koe Hwee *; Yeoh, K. K. (Universiti Malaysia Sarawak, 2021)
Financial planning for marriage contributes to happier, more satisfying and longer-lasting unions. However, there is increasing evidence that young Malaysian couples are burdened by excessive debts and have a tendency to overspend on their wedding. Based on the Theory of Planned Behaviour, the current study investigates key factors — financial literacy, attitude towards money, attitude towards debt, financial goals and social influence — that are likely to influence the degree of financial planning for marriage undertaken by married and soon-to-be-married couples. The study also examines the mediating role of financial literacy on the relationships between the aforementioned key factors and financial planning for marriage. The study collected data from a sample of 201 respondents recruited via purposive sampling and used a bootstrapped partial least squares structural equation modelling (PLS-SEM) approach for data analysis. The results showed that (i) financial literacy positively influences financial planning for marriage; (ii) attitude towards money, financial goals and social influence positively influence both financial literacy and financial planning for marriage; (iii) attitude towards debt has a negative influence on financial planning for marriage but no influence on financial literacy; and (iv) financial literacy has a mediating effect. The findings highlight the importance of financial counselling, education as well as discipline in bringing about successful marriages.